2001
DOI: 10.1007/s004020000202
|View full text |Cite
|
Sign up to set email alerts
|

Midshaft fractures of the clavicle with a shortening of more than 2 cm predispose to nonunion

Abstract: Up to 15% of all fractures involve the clavicle. Nonunion of the clavicle is a rare complication after conservative treatment. It mainly presents as pain at the fracture site and a limited range of motion of the shoulder. The purpose of this study is to define a certain type of fracture of the clavicle that is predisposed to malunion and therefore should be treated surgically after failure of conservative treatment. Thirty-nine patients with delayed or malunion of the clavicle were analyzed. There were 13 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
74
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(87 citation statements)
references
References 19 publications
1
74
0
8
Order By: Relevance
“…It has been shown that middle-third clavicle fractures with more than two cm of displacement or 15 mm of shortening are at increased risk for nonunion [7,15]. Thompson reviewed more than 100 middle-third clavicular nonunions reported in the literature and found that 90% of the original fractures had displacement greater than 100%, overriding more than one cm, or had severe comminution [11,16]. Although fractures with this much displacement are uncommon, accounting for 3% of all middle-third clavicle fractures, they warrant open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that middle-third clavicle fractures with more than two cm of displacement or 15 mm of shortening are at increased risk for nonunion [7,15]. Thompson reviewed more than 100 middle-third clavicular nonunions reported in the literature and found that 90% of the original fractures had displacement greater than 100%, overriding more than one cm, or had severe comminution [11,16]. Although fractures with this much displacement are uncommon, accounting for 3% of all middle-third clavicle fractures, they warrant open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…7) Displaced fracture of the clavicular midshaft shows a higher rate of delayed and nonunion than nondisplaced fracture patterns. [8][9][10][11][12][13][14] However, with the development of plates such as low-profile LCP, more stable fixation is possible and good results have been reported after surgical treatment in clavicle midshaft fracture. 4,5) 15) suggested leaving a plate in place for 12 to 18 months and placement of restrictions against contact sports for 2 to 3 months after plate removal.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Zlowodzki et al 18) found that in 159 patients who received conservative treatment around 15.1% showed non-union. Wick et al 19) found that a high prevalence of diastasis was associated with patients who received conservative treatment for clavicle shaft fractures, which may have led to the decreased clinical outcome with a nonunion rate of 10% to 15%. Therefore, it is becoming more evident that conservative measures alone may not be sufficient for the treatment of clavicular fractures.…”
Section: Discussionmentioning
confidence: 99%